A 3D In Vivo Model for Studying Human Renal Cystic Tissue and Mouse Kidney Slices - Bichlmayer, Eva Marie; Mahl, Lina; Hesse, Leo; Pion, Eric; Haller, Victoria; Moehwald, Andreas; Hackl, Christina; Werner, Jens M.; Schlitt, Hans J.; Schwarz, Siegfried; Kainz, Philipp; Brochhausen, Christoph; et al. (Cells, 2022)
(1) Background: Autosomal dominant polycystic kidney disease (ADPKD) is a frequent monogenic disorder that leads to progressive renal cyst growth and renal failure. Strategies to inhibit cyst growth in non-human cyst models have often failed in clinical trials. There is a significant need for models that enable studies of human cyst growth and drug trials. (2) Methods: Renal tissue from ADPKD patients who received a nephrectomy as well as adult mouse kidney slices were cultured on a chorioallantoic membrane (CAM) for one week. The cyst volume was monitored by microscopic and CT-based applications. The weight and angiogenesis were quantified. Morphometric and histological analyses were performed after the removal of the tissues from the CAM. (3) Results: The mouse and human renal tissue mostly remained vital for about one week on the CAM. The growth of cystic tissue was evaluated using microscopic and CT-based volume measurements, which correlated with weight and an increase in angiogenesis, and was accompanied by cyst cell proliferation. (4) Conclusions: The CAM model might bridge the gap between animal studies and clinical trials of human cyst growth, and provide a drug-testing platform for the inhibition of cyst enlargement. Real-time analyses of mouse kidney tissue may provide insights into renal physiology and reduce the need for animal experiments.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 3D in vivo model; ADPKD; chorioallantoic membrane (CAM) model; human renal cystic tissue; mouse kidney slices; polycystic kidney disease

Aberrant Ca2+signals in ADPKD activate TMEM16A and Cyst Growth - Cabrita, I.; Buchholz, Björn; Schreiber, R.; Kunzelmann, K. (Acta Physiologica, 2019)

A Fluorescent Benzo[g]isoquinoline-based HIF Prolyl Hydroxylase Inhibitor for Cellular Imaging. - Mayer, Marleen; Fey, Kerstin; Heinze, Eva; Wick, Christian; Abboud, Martine I.; Yeh, Tzu Lan; Tumber, Anthony; Orth, Nicole; Schley, Gunnar; Buchholz, Björn; Clark, Timothy; Schofield, Christopher J.; et al. (ChemMedChem, 2018)
Prolyl hydroxylation domain enzymes (PHD) catalyze the hydroxylation of the transcription factor Hypoxia Inducible Factor (HIF) and serve as cellular oxygen sensors. HIF and the PHD enzymes regulate numerous potentially tissue protective target genes which can adapt cells to metabolic and ischemic stress. We describe a fluorescent PHD inhibitor (1-chloro-4-hydroxybenzo[g]isoquinoline-3-carbonyl)-glycine which is suited to fluorescent based detection assays and for monitoring PHD inhibitors in biological systems. In cell based assays, application of the fluorescent PHD inhibitor allowed co-localization with a cellular PHD enzyme and led to live cell imaging of processes involved in cellular oxygen sensing.
Keywords: fluorescence microscopy; HIF system; hypoxia; oxygen sensing; PHD inhibitors

An inwardly rectifying whole cell current induced by G(q)-coupled receptors - Buchholz, Björn; Tauber, Robert; Steffl, Daniel; Walz, Gerd; Koettgen, Michael (Biochemical and Biophysical Research Communications, 2004)
Ca2+ influx across the plasma membrane after stimulation of G protein-coupled receptors is important for many physiological functions. Here we studied the regulation of an inwardly rectifying whole cell current and its putative role in Ca2+ entry in Xenopus oocytes. Expression of P2Y(1) or M1 receptors in Xenopus oocytes elicited a characteristic inwardly rectifying current without receptor stimulation. This current displayed distinct activation and inactivation kinetics and was highly Ca2+-dependent. After stimulation of endogenous G(q)-coupled receptors in water-injected cells similar currents were observed. We therefore speculated that the current could be activated via Ca2+ store depletion induced by constitutive stimulation of the IP3 cascade in cells overexpressing G(q)-coupled receptors. Receptor-independent Ca2+ store depletion also induced the current. In conclusion, this current is activated after store depletion suggesting a role in Ca2+ entry after stimulation of G(q)-coupled receptors. Finally, our data do not support the proposed ionotropic properties of the P2Y(1) receptor. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: G protein-coupled receptor; P2Y receptor; M1 receptor; Xenopus oocyte; store depletion; Ca2+ signaling; IP3; cascade; capacitative Ca2+ entry

Anoctamin 1 induces calcium-activated chloride secretion and proliferation of renal cyst-forming epithelial cells - Buchholz, Björn; Faria, Diana; Schley, Gunnar; Schreiber, Rainer; Eckardt, Kai-Uwe; Kunzelmann, Karl (Kidney International, 2014)
Polycystic kidney diseases are characterized by multiple bilateral renal cysts that gradually enlarge and lead to a decline in renal function. Cyst enlargement is driven by transepithelial chloride secretion, stimulated by enhanced levels of cyclic adenosine monophosphate, which activates apical cystic fibrosis transmembrane conductance regulator chloride channels. However, chloride secretion by calcium-dependent chloride channels, activated through stimulation of purinergic receptors, also has a major impact. To identify the molecular basis of calcium-dependent chloride secretion in cyst expansion, we determined the role of anoctamin 1 and 6, two recently discovered calcium-activated chloride channels both of which are expressed in epithelial cells. We found that anoctamin 1, which plays a role in epithelial fluid secretion and proliferation, is strongly expressed in principal-like MDCK cells (PLCs) forming cysts within a collagen matrix, in an embryonic kidney cyst model, and in human autosomal dominant polycystic kidney disease tissue. Knockdown of anoctamin 1 but not anoctamin 6 strongly diminished the calcium-dependent chloride secretion of PLCs. Moreover, two inhibitors of anoctamin ion channels, tannic acid and a more selective inhibitor of anoctamin 1, significantly inhibited PLC cyst growth and cyst enlargement in an embryonic kidney cyst model. Knockdown of ANO1 by morpholino analogs also attenuated embryonic cyst growth. Thus, calcium-activated chloride secretion by anoctamin 1 appears to be a crucial component of renal cyst growth.
EVALuna2:3642

Anoctamin 6 is localized in the primary cilium of renal tubular cells and is involved in apoptosis-dependent cyst lumen formation - Forschbach, V.; Goppelt-Strübe, Margarete; Kunzelmann, K.; Schreiber, R.; Piedagnel, Remi; Kraus, Andre; Eckardt, Kai-Uwe; Buchholz, Björn (Cell Death & Disease, 2015)
Primary cilia are antenna-like structures projected from the apical surface of various mammalian cells including renal tubular cells. Functional or structural defects of the cilium lead to systemic disorders comprising polycystic kidneys as a key feature. Here we show that anoctamin 6 (ANO6), a member of the anoctamin chloride channel family, is localized in the primary cilium of renal epithelial cells in vitro and in vivo. ANO6 was not essential for cilia formation and had no effect on in vitro cyst expansion. However, knockdown of ANO6 impaired cyst lumen formation of MDCK cells in three-dimensional culture. In the absence of ANO6, apoptosis was reduced and epithelial cells were incompletely removed from the center of cell aggregates, which form in the early phase of cystogenesis. In line with these data, we show that ANO6 is highly expressed in apoptotic cyst epithelial cells of human polycystic kidneys. These data identify ANO6 as a cilium-associated protein and suggest its functional relevance in cyst formation.

Anoctamins control Ca2+ signaling in micro domains of plasma membranes and are expressed in the primary cilium - Schreiber, R.; Cabrita, I.; Fonseca, A.; Benedetto, R.; Wanitchakod, P.; Sirianant, L.; Forschbach, V.; Buchholz, Björn; Kunzeimann, K. (Acta Physiologica, 2017)

A novel direct adenosine monophosphate kinase activator ameliorates disease progression in preclinical models of Autosomal Dominant Polycystic Kidney Disease - Dagorn, Pascale Gluais; Buchholz, Björn; Kraus, Andre; Batchuluun, Battsetseg; Bange, Hester; Blockken, Laura; Steinberg, Gregory R.; Moller, David E.; Hallakou-Bozec, Sophie (Kidney International, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) mainly results from mutations in the PKD1 gene, which encodes polycystin 1. It is the most common inherited kidney disease and is characterized by a progressive bilateral increase in cyst number and size, often leading to kidney failure. The cellular energy sensor and regulator adenosine monophosphate stimulated protein kinase (AMPK) has been implicated as a promising new therapeutic target. To address this hypothesis, we determined the effects of a potent and selective clinical stage direct allosteric AMPK activator, PXL770, in canine and patient-derived 3D cyst models and an orthologous mouse model of ADPKD. PXL770 induced AMPK activation and dose-dependently reduced cyst growth in principal-like Madin-Darby Canine Kidney cells stimulated with forskolin and kidney epithelial cells derived from patients with ADPKD stimulated with desmopressin. In an inducible, kidney epithelium-specific Pkd1 knockout mouse model, PXL770 produced kidney AMPK pathway engagement, prevented the onset of kidney failure (reducing blood urea by 47%), decreased cystic index by 26% and lowered the kidney weight to body weight ratio by 35% compared to untreated control Pkd1 knockout mice. These effects were accompanied by a reduction of markers of cell proliferation (-48%), macrophage infiltration (-53%) and tissue fibrosis (-37%). Thus, our results show the potential of direct allosteric AMPK activation in the treatment of ADPKD and support the further development of PXL770 for this indication.
CRIS-Team Scopus Importer:2023-04-21
Keywords: ADPKD; AMPK; fibrosis; inflammation; mitochondria; PXL770

Cyst growth in ADPKD is prevented by pharmacological and genetic inhibition of TMEM16A in vivo - Cabrita, Ines; Kraus, Andre; Scholz, Julia Katharina; Skoczynski, Kathrin; Schreiber, Rainer; Kunzelmann, Karl; Buchholz, Björn (Nature Communications, 2020)
In autosomal dominant polycystic kidney disease (ADPKD) multiple bilateral renal cysts gradually enlarge, leading to a decline in renal function. Transepithelial chloride secretion through cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1) are known to drive cyst enlargement. Here we demonstrate that loss of Pkd1 increased expression of TMEM16A and CFTR and Cl− secretion in murine kidneys, with TMEM16A essentially contributing to cyst growth. Upregulated TMEM16A enhanced intracellular Ca2+ signaling and proliferation of Pkd1-deficient renal epithelial cells. In contrast, increase in Ca2+ signaling, cell proliferation and CFTR expression was not observed in Pkd1/Tmem16a double knockout mice. Knockout of Tmem16a or inhibition of TMEM16A in vivo by the FDA-approved drugs niclosamide and benzbromarone, as well as the TMEM16A-specific inhibitor Ani9 largely reduced cyst enlargement and abnormal cyst cell proliferation. The present data establish a therapeutic concept for the treatment of ADPKD.
CRIS-Team Scopus Importer:2020-09-04

Donor treatment with a PHD-inhibitor activating HIFs prevents graft injury and prolongs survival in an allogenic kidney transplant model - Bernhardt, W. M.; Gottmann, U.; Doyon, F.; Buchholz, Björn; Campean, Valentina; Schödel, Johannes; Reisenbuechler, A.; Klaus, S.; Arend, M.; Flippin, L.; Willam, Carsten; Yard, B.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Long-term survival of renal allografts depends on the chronic immune response and is probably influenced by the initial injury caused by ischemia and reperfusion. Hypoxia-inducible transcription factors (HIFs) are essential for adaptation to low oxygen. Normoxic inactivation of HIFs is regulated by oxygen-dependent hydroxylation of specific prolyl-residues by prolyl-hydroxylases (PHDs). Pharmacological inhibition of PHDs results in HIF accumulation with subsequent activation of tissue-protective genes. We examined the effect of donor treatment with a specific PHD inhibitor (FG-4497) on graft function in the Fisher-Lewis rat model of allogenic kidney transplantation (KTx). Orthotopic transplantation of the left donor kidney was performed after 24 h of cold storage. The right kidney was removed at the time of KTx (acute model) or at day 10 (chronic model). Donor animals received a single dose of FG-4497 (40 mg/kg i.v.) or vehicle 6 h before donor nephrectomy. Recipients were followed up for 10 days (acute model) or 24 weeks (chronic model). Donor preconditioning with FG-4497 resulted in HIF accumulation and induction of HIF target genes, which persisted beyond cold storage. It reduced acute renal injury (serum creatinine at day 10: 0.66 +/- 0.20 vs. 1.49 +/- 1.36 mg/dL; P < 0.05) and early mortality in the acute model and improved long-term survival of recipient animals in the chronic model (mortality at 24 weeks: 3 of 16 vs. 7 of 13 vehicle-treated animals; P < 0.05). In conclusion, pretreatment of organ donors with FG-4497 improves short-and long-term outcomes after allogenic KTx. Inhibition of PHDs appears to be an attractive strategy for organ preservation that deserves clinical evaluation.
Keywords: hypoxia-inducible transcription factors; kidney injury; protection; transplantation

Formation of cysts by principal-like MDCK cells depends on the synergy of cAMP- and ATP-mediated fluid secretion - Buchholz, Björn; Teschemacher, Barbara; Schley, Gunnar; Schillers, Hermann; Eckardt, Kai-Uwe (Journal of Molecular Medicine, 2011)
It has been suggested that more than 70% of the renal cysts in patients with autosomal dominant polycystic kidney disease (ADPKD) arise from the collecting duct and that within this segment cysts originate almost exclusively from principal rather than intercalated cells. The mechanisms for this predisposition of principal cells have so far remained elusive. We, therefore, used Madin-Darby canine kidney (MDCK) subclones resembling principal cells and alpha-intercalated cells in a three-dimensional in vitro model to determine differences in cystogenesis and cyst growth, including the response to cyclic adenosine monophosphate (cAMP) elevation and the dependence on ATP signaling. We found that in vitro cysts developed only from principal-like but not from intercalated-like MDCK cell clones. This specificity could be verified in mixed MDCK cultures enriched for principal- or intercalated-like cells. In vitro cyst growth upon elevation of intracellular cAMP was mainly driven by fluid secretion, rather than increased cell proliferation. The cAMP-dependent fluid secretion was found to depend on extracellular adenosine-5'-triphosphate (ATP) and to act synergistically with purinergic signaling, as the use of the ATP scavenger apyrase, as well as the P2 receptor inhibitor suramin, reduced cAMP-driven fluid secretion, while increasing extracellular ATP potentiated cAMP-mediated cyst growth. In conclusion, we provide in vitro evidence for the ability of principal rather than intercalated cells to form cysts, based on a synergism of cAMP and ATP signaling in enhancing apical fluid secretion.
Keywords: ATP; cAMP; Collecting duct cells; Cystogenesis; Intercalated cells; Principal cells

Glucose promotes secretion-dependent renal cyst growth. - Kraus, Andre; Schley, Gunnar; Kunzelmann, Karl; Schreiber, Rainer; Peters, Dorien J. M.; Stadler, Ruth; Eckardt, Kai-Uwe; Buchholz, Björn (Journal of Molecular Medicine, 2016)
Polycystic kidney diseases are characterized by the development of numerous bilateral renal cysts that continuously enlarge resulting in a decline of kidney function due to compression of intact nephrons. Cyst growth is driven by transepithelial chloride secretion which depends on both intracellular cAMP and calcium. Mechanisms that are involved in the regulation of the underlying secretory pathways remain incompletely understood. Here we show that glucose concentration has a strong impact on cyst growth of renal tubular cells within a collagen matrix as well as in embryonic kidneys deficient or competent for Pkd1. Glucose-dependent cyst growth correlates with the transcriptional induction of the calcium-activated chloride channel anoctamin 1 (ANO1) and its increased expression in the apical membrane of cyst-forming cells. Inhibition of ANO1 with the specific inhibitor CaCCinh-AO1 significantly decreases glucose-dependent cyst growth in both models. Ussing chamber analyses revealed increased apical chloride secretion of renal tubular cells upon exposure to high glucose medium which can also be inhibited by the use of CaCCinh-AO1. These data suggest that glycemic control may help to reduce renal cyst growth in patients with polycystic kidney disease.Renal cyst growth depends on glucose concentration in two in vitro cyst models. High glucose leads to upregulation of the calcium-activated chloride channel ANO1. High glucose promotes calcium-activated chloride secretion via ANO1. Glucose-dependent secretion can be inhibited by a specific inhibitor of ANO1.
EVALuna2:3791
Keywords: Polycystic kidney disease; Cyst growth; Chloride secretion; Glucose; Diabetes mellitus type 2; Anoctamin 1

HIF-1α promotes cyst progression in a mouse model of autosomal dominant polycystic kidney disease - Kraus, Andre; Peters, Dorien J. M.; Klanke, Bernd; Weidemann, Alexander; Willam, Carsten; Schley, Gunnar; Kunzelmann, Karl; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2018)
Autosomal dominant polycystic kidney disease (ADPKD) is mainly caused by mutations of the PKD1 gene and characterized by growth of bilateral renal cysts. Cyst growth is accompanied by regional hypoxia and induction of hypoxia-inducible factor (HIF)-1α in cyst-lining epithelial cells. To determine the relevance of HIF-1α for cyst growth in vivo we used an inducible kidney epithelium-specific knockout mouse to delete Pkd1 at postnatal day 20 or 35 to induce polycystic kidney disease of different severity and analyzed the effects of Hif-1α co-deletion and HIF-1α stabilization using a prolyl-hydroxylase inhibitor. HIF-1α expression was enhanced in kidneys with progressive cyst growth induced by early Pkd1 deletion, but unchanged in the milder phenotype induced by later Pkd1 deletion. Hif-1α co-deletion significantly attenuated cyst growth in the severe, but not in the mild, phenotype. Application of a prolyl-hydroxylase inhibitor resulted in severe aggravation of the mild phenotype with rapid loss of renal function. HIF-1α expression was associated with induction of genes that mediate calcium-activated chloride secretion. Thus, HIF-1α does not seem to play a role in early cyst formation, but accelerates cyst growth during progressive polycystic kidney disease. This novel mechanism of cyst growth may qualify as a therapeutic target.
EVALuna2:215684
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; polycystic kidney disease; prolyl-hydroxylase inhibitors

HIF activation protects from acute kidney injury - Weidemann, Alexander; Bernhardt, Wanja M.; Klanke, Bernd; Daniel, Christoph; Buchholz, Björn; Campean, Valentina; Amann, Kerstin Ute; Warnecke, Christina; Wiesener, Michael Sean; Eckardt, Kai-Uwe; Willam, Carsten (Journal of the American Society of Nephrology, 2008)
The contribution of hypoxia to cisplatin-induced renal tubular injury is controversial. Because the hypoxia-inducible factor (HIF) pathway is a master regulator of adaptation to hypoxia, we measured the effects of cisplatin on HIF accumulation in vitro and in vivo, and tested whether hypoxic preconditioning is protective against cisplatin-induced injury. We found that cisplatin did not stabilize HIF-1 alpha protein in vitro or in vivo under normoxic conditions. However, hypoxic preconditioning of cisplatin-treated proximal tubular cells in culture reduced apoptosis in an HIF-1 alpha-dependent fashion and increased cell proliferation as measured by BrdU incorporation. In vivo, rats preconditioned with carbon monoxide before cisplatin administration had significantly better renal function than rats kept in normoxic conditions throughout. Moreover, the histomorphological extent of renal damage and tubular apoptosis was reduced by the preconditional treatment. Therefore, development of pharmacologic agents to induce renal HIF might provide a new approach to ameliorate cisplatin-induced nephrotoxicity.

Hypoxia induces polycystin-1 expression in the renal epithelium - Grampp, Steffen; Kraus, Andre; Skoczynski, Kathrin; Schiffer, Mario; Krüger, René; Naas, Stephanie; Schödel, Johannes; Buchholz, Björn (Royal Society Open Science, 2023)
Mutations in polycystin-1 which is encoded by the PKD1 gene are the main causes for the development of autosomal dominant polycystic kidney disease. However, only little is known about the physiological function of polycystin-1 and even less about the regulation of its expression. Here, we show that expression of PKD1 is induced by hypoxia and compounds that stabilize the hypoxia-inducible transcription factor (HIF) 1α in primary human tubular epithelial cells. Knockdown of HIF subunits confirms HIF-1α-dependent regulation of polycystin-1 expression. Furthermore, HIF ChIP-seq reveals that HIF interacts with a regulatory DNA element within the PKD1 gene in renal tubule-derived cells. HIF-dependent expression of polycystin-1 can also be demonstrated in vivo in kidneys of mice treated with substances that stabilize HIF. Polycystin-1 and HIF-1α have been shown to promote epithelial branching during kidney development. In line with these findings, we show that expression of polycystin-1 within mouse embryonic ureteric bud branches is regulated by HIF. Our finding links expression of one of the main regulators of accurate renal development with the hypoxia signalling pathway and provides additional insight into the pathophysiology of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-06-30
Keywords: hypoxia; hypoxia-inducible factor; kidney development; PKD1; polycystic kidney disease; transcription regulation

Hypoxia-inducible factor-1α causes renal cyst expansion through calcium-activated chloride secretion - Willam, Carsten; Eckhardt, Kai-Uwe; Buchholz, Björn; Schley, Gunnar; Faria, Diana; Kroening, Sven; Willam, Carsten; Schreiber, Rainer; Klanke, Bernd; Burzlaff, Nicolai; Jantsch, Jonathan; Kunzelmann, Karl; et al. (Journal of the American Society of Nephrology, 2014)
Polycystic kidney diseases are characterized by numerous bilateral renal cysts that continuously enlarge and, through compression of intact nephrons, lead to a decline in kidney function over time. We previously showed that cyst enlargement is accompanied by regional hypoxia, which results in the stabilization of hypoxia-inducible transcription factor-1α (HIF-1α) in the cyst epithelium. Here we demonstrate a correlation between cyst size and the expression of the HIF-1α-target gene, glucose transporter 1, and report that HIF-1α promotes renal cyst growth in two in vitro cyst models - principal-like MDCK cells (plMDCKs) within a collagen matrix and cultured embryonic mouse kidneys stimulated with forskolin. In both models, augmenting HIF-1α levels with the prolyl hydroxylase inhibitor 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate enhanced cyst growth. In addition, inhibition of HIF-1α degradation through tubule-specific knockdown of the von Hippel-Lindau tumor suppressor increased cyst size in the embryonic kidney cyst model. In contrast, inhibition of HIF-1α by chetomin and knockdown of HIF-1α both decreased cyst growth in these models. Consistent with previous reports, plMDCK cyst enlargement was driven largely by transepithelial chloride secretion, which consists, in part, of a calcium-activated chloride conductance. plMDCKs deficient for HIF-1α almost completely lacked calcium-activated chloride secretion. We conclude that regional hypoxia in renal cysts contributes to cyst growth, primarily due to HIF-1α-dependent calcium-activated chloride secretion. These findings identify the HIF system as a novel target for inhibition of cyst growth. Copyright © 2014 by the American Society of Nephrology.

Hypoxia inducible factor stabilization improves defective ischemia-induced angiogenesis in a rodent model of chronic kidney disease - Schellinger, Isabel Nahal; Cordasic, Nada; Panesar, Julian; Buchholz, Björn; Jacobi, Johannes; Hartner, Andrea; Klanke, Bernd; Jakubiczka-Smorag, Joanna; Burzlaff, Nicolai; Heinze, Eva; Warnecke, Christina; Raaz, Uwe; et al. (Kidney International, 2017)
Chronic kidney disease (CKD) is associated with increased risk and worse prognosis of cardiovascular disease, including peripheral artery disease. An impaired angiogenic response to ischemia may contribute to poor outcomes of peripheral artery disease in patients with CKD. Hypoxia inducible factors (HIF) are master regulators of angiogenesis and therefore represent a promising target for therapeutic intervention. To test this we induced hind-limb ischemia in rats with CKD caused by 5/6 nephrectomy and administered two different treatments known to stabilize HIF protein in vivo: carbon monoxide and a pharmacological inhibitor of prolyl hydroxylation 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate (ICA). Expression levels of pro-angiogenic HIF target genes (Vegf, Vegf-r1, Vegf-r2, Ho-1) were measured by qRT-PCR. Capillary density was measured by CD31 immunofluorescence staining and HIF expression was evaluated by immunohistochemistry. Capillary density in ischemic skeletal muscle was significantly lower in CKD animals compared to sham controls. Rats with CKD showed significantly lower expression of HIF and all measured pro-angiogenic HIF target genes, including VEGF. Both HIF stabilizing treatments rescued HIF target gene expression in animals with CKD and led to significantly higher ischemia-induced capillary sprouting compared to untreated controls. ICA was effective regardless of whether it was administered before or after induction of ischemia and led to a HIF expression in skeletal muscle. Thus, impaired ischemia-induced angiogenesis in rats with CKD can be improved by HIF stabilization, even if started after onset of ischemia.
EVALuna2:3925
Keywords: cardiovascular disease; chronic kidney disease; hypoxia

Hypoxia inhibits nephrogenesis through paracrine Vegfa despite the ability to enhance tubulogenesis - Schley, Gunnar; Scholz, Holger; Kraus, Andre; Hackenbeck, Thomas; Klanke, Bernd; Willam, Carsten; Wiesener, Michael; Heinze, Eva; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2015)
Reduced nephron number predisposes to hypertension and kidney disease. Interaction of the branching ureteric bud and surrounding mesenchymal cells determines nephron number. Since oxygen supply may be critical for intrauterine development, we tested whether hypoxia and hypoxiainducible factor-1 alpha (HIF-1 alpha) influence nephrogenesis. We found that HIF-1 alpha is required for branching of MDCK cells. In addition, culture of metanephric mouse kidneys with ureteric bud cell-specific stabilization or knockout of HIF-1 alpha revealed a positive impact of HIF-1 alpha on nephrogenesis. In contrast, widespread stabilization of HIF-1 alpha in metanephric kidneys through hypoxia or HIF stabilizers impaired nephrogenesis, and pharmacological HIF inhibition enhanced nephrogenesis. Several lines of evidence suggest an inhibitory effect through the hypoxia response of mesenchymal cells. HIF-1 alpha was expressed in mesenchymal cells during nephrogenesis. Expression of the anti-branching factors Bmp4 and Vegfa, secreted by mesenchymal cells, was increased upon HIF stabilization. The conditioned medium from hypoxic metanephric kidneys inhibited MDCK branching, which was partially rescued by Vegfa antibodies. Thus, the effect of HIF-1 alpha on nephrogenesis appears context dependent. While HIF-1 alpha in the ureteric bud is of importance for proper branching morphogenesis, the net effect of hypoxia-induced HIF activation in the embryonic kidney appears to be mesenchymal cell-dependent inhibition of ureter branching.
EVALuna2:3775
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; kidney development; metanephric mesenchyme; nephrogenesis; Vegfa

Increased Expression of Secreted Frizzled-Related Protein 4 in Polycystic Kidneys - Romaker, Daniel; Puetz, Michael; Teschner, Sven; Donauer, Johannes; Geyer, Marcel; Gerke, Peter; Rumberger, Brigitta; Dworniczak, Bernd; Pennekamp, Petra; Buchholz, Björn; Neumann, H. P. H.; Kumar, Rajiv; et al. (Journal of the American Society of Nephrology, 2009)
Autosomal dominant polycystic kidney disease (ADPKD) is a common hereditary disease associated with progressive renal failure. Although cyst growth and compression of surrounding tissue may account for some loss of renal tissue, the other factors contributing to the progressive renal failure in patients with ADPKD are incompletely understood. Here, we report that secreted frizzled-related protein 4 (sFRP4) is upregulated in human ADPKD and in four different animal models of PKD, suggesting that sFRP4 expression is triggered by a common mechanism that underlies cyst formation. Cyst fluid from ADPKD kidneys activated the sFRP4 promoter and induced production of sFRP4 protein in renal tubular epithelial cell lines. Antagonism of the vasopressin 2 receptor blocked both promoter activity and tubular sFRP4 expression. In addition, sFRP4 selectively influenced members of the canonical Writ signaling cascade and promoted cystogenesis of the zebrafish pronephros. sFRP4 was detected in the urine of both patients and animals with PKD, suggesting that sFRP4 may be a potential biomarker for monitoring the progression of ADPKD. Taken together, these observations suggest a potential role for SFRP4 in the pathogenesis of ADPKD.

In vitro cyst puncture and injury-induced tubule formation using renal epithelial cells - Kraus, Andre; Lüdke, Andrea; Teschemacher, Barbara; Skoczynski, Kathrin; Buchholz, Björn (STAR Protocols, 2023)
Collecting-duct-derived renal epithelial cells switch from tubule to cyst formation; however, the cysts still form tubules after injury of the cyst-lining epithelium. Here, we provide a protocol that describes in vitro cyst growth with focus on glass-capillary-induced cyst wall injury to induce tubule formation. We detail steps for the establishment of the in vitro cyst assay, followed by puncture of the cysts in the collagen matrix. We further describe live imaging and steps to analyze the tubule growth. For complete details on the use and execution of this protocol, please refer to Scholz et al. (2022).1
CRIS-Team Scopus Importer:2023-02-03
Keywords: Cell Biology; Cell culture; Cell-based Assays; Microscopy

Isolated thrombotic microangiopathy of the small intestine in a patient with atypical hemolytic uremic syndrome - a case report - Nunius, Christoph; Büttner-Herold, Maike; Bertz, Simone; Schiffer, Mario; Buchholz, Björn (BMC Nephrology, 2020)
Background: Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by systemic thrombotic microangiopathy (TMA) reflected by hemolysis, anemia, thrombocytopenia and systemic organ injury. The optimal management of aHUS-patients when undergoing kidney transplantation to prevent recurrence in the allograft is eculizumab, an approved recombinant antibody targeting human complement component C5. Case presentation: A 39 year-old woman presented with severe abdominal pain, diarrhea and emesis for 3 days. In her past medical history she had experienced an episode of aHUS leading to end stage renal disease (ESRD) in 2007 and a genetic workup revealed a heterozygous mutation in the membrane cofactor protein gene. In 2014 she underwent cadaveric kidney transplantation. Four years later she had to go back on hemodialysis due to allograft failure following a severe systemic cytomegalovirus infection resulting in transplant failure. At presentation she still received calcineurin-inhibitor therapy and reported subfebrile temperatures and pain projecting over the transplant prior to the current symptoms. A contrast enhanced CT-scan of the abdomen revealed inflammatory wall thickening of the small intestine. Diagnostic endoscopy discovered fresh blood in the small intestine without a clear source of bleeding. Histopathology of the small intestine biopsies showed severe thrombotic microangiopathy. Of note, the patient persistently had no signs of systemic hemolysis. Since the TMA of the small intestine was most likely due to aHUS, eculizumab treatment was initiated which abolished the symptoms. Conclusion: Here we report a patient with thrombotic microangiopathy with predominant manifestation in a single organ, the small intestine, due to aHUS with absence of systemic signs and symptoms. aHUS patients usually require a secondary trigger for the disease to manifest. In this case, the trigger may be attributed to the dysfunctional renal transplant, which was subsequently explanted. Histology of the explanted kidney showed severe inflammation due to purulent nephritis and signs of cellular rejection. After nephrectomy, we continued eculizumab therapy until the patient completely recovered. No signs of TMA recurred after discontinuation of eculizumab, further supporting the concept of the renal transplant as the main trigger of TMA of the small intestine in our patient.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atypical hemolytic uremic syndrome; Case report; Renal transplant; Small intestine; Thrombotic microangiopathy

Kif3a Guides Microtubular Dynamics, Migration and Lumen Formation of MDCK Cells - Boehlke, Christopher; Kotsis, Fruzsina; Buchholz, Björn; Powelske, Christian; Eckardt, Kai-Uwe; Walz, Gerd; Nitschke, Roland; Kuehn, E. Wolfgang (PLoS ONE, 2013)
The microtubular motor Kinesin-2 and its subunit Kif3a are essential for the formation of primary cilia, an organelle implicated in a wide spectrum of developmental abnormalities. Outside cilia, Kinesin-2 mediated transport has been implicated in vesicle and N-cadherin transport, but it is unknown if and how extraciliary Kif3a affects basic cellular functions such as migration or the formation of multicellular structures. Here we show that tetracycline inducible depletion of Kif3a in MDCK cells slows epithelial cell migration. Microtubules at the leading edge of Kif3a depleted cells failed to grow perpendicularly into the leading edge and microtubular dynamics were dampened in Kif3a depleted cells. Loss of Kif3a retarded lateral membrane specification and completely prevented the formation of three-dimensional spheres in collagen. These data uncover that Kif3a regulates the microtubular cytoskeleton in the cell periphery and imply that extra-ciliary Kif3a has an unexpected function in morphogenesis.

Lipid Peroxidation Drives Renal Cyst Growth In Vitro through Activation of TMEM16A - Schreiber, Rainer; Buchholz, Björn; Kraus, Andre; Schley, Gunnar; Scholz, Julia; Ousingsawat, Jiraporn; Kunzelmann, Karl (Journal of the American Society of Nephrology, 2019)
Background Transepithelial chloride2 secretion, through the chloride channels cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1), drives cyst enlargement in polycystic kidney disease (PKD). Polycystic kidneys are hypoxic, and oxidative stress activates TMEM16A. However, mechanisms for channel activation in PKD remain obscure.Methods Using tissue samples from patients with autosomal dominant PKD, embryonic kidney cultures, and anMDCK in vitro cyst model, we assessed peroxidation of plasmamembrane phospholipids in human and mouse polycystic kidneys. We also used electrophysiologic Ussing chamber and patch clamp experiments to analyze activation of TMEM16A and growth of renal cysts.Results Peroxidation of phospholipids in human and mouse kidneys as well as MDCK cysts in vitro is probably due to enhanced levels of reactive oxygen species. Lipid peroxidation correlated with increased cyst volume as shown in renal cultures and MDCK cysts in three-dimensional cultures. Reactive oxygen species and lipid peroxidation strongly activated TMEM16A, leading to depletion of calciumion stores and store-operated calcium influx. Activation of TMEM16A-and CFTR-dependent chloride secretion strongly augmented cyst growth. Exposure to scavengers of reactive oxygen species, such as glutathione, coenzyme Q10, or idebenone (a synthetic coenzyme Q10 homolog), as well as inhibition of oxidative lipid damage by ferrostatin-1 largely reduced activation of TMEM16A. Inhibition of TMEM16A reduced proliferation and fluid secretion in vitro.Conclusions These findings indicate that activation of TMEM16A by lipid peroxidation drives growth of renal cysts. We propose direct inhibition of TMEM16A or inhibition of lipid peroxidation as potentially powerful therapeutic approaches to delay cyst development in PKD.
CRIS-Team WoS Importer:2019-02-27
Keywords: ADPKD; TMEM16A; reactive oxygen species; lipid peroxidation; ferroptosis; anoctamin 1

Loss of Polycystin-1 causes cAMP-dependent switch from tubule to cyst formation. - Scholz, Julia; Kraus, Andre; Lueder, Dominik; Skoczynski, Kathrin; Schiffer, Mario; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (iScience, 2022)
Autosomal dominant polycystic kidney disease is the most common monogenic disease that causes end-stage renal failure. It primarily results from mutations in the PKD1 gene that encodes for Polycystin-1. How loss of Polycystin-1 translates into bilateral renal cyst development is mostly unknown. cAMP is significantly involved in cyst enlargement but its role in cyst initiation has remained elusive. Deletion of Polycystin-1 in collecting duct cells resulted in a switch from tubule to cyst formation and was accompanied by an increase in cAMP. Pharmacological elevation of cAMP in Polycystin-1-competent cells caused cyst formation, impaired plasticity, nondirectional migration, and mis-orientation, and thus strongly resembled the phenotype of Polycystin-1-deficient cells. Mis-orientation of developing tubule cells in metanephric kidneys upon loss of Polycystin-1 was phenocopied by pharmacological increase of cAMP in wildtype kidneys. In vitro, cAMP impaired tubule formation after capillary-induced injury which was further impaired by loss Polycystin-1.
EVALuna2:505609

Macrophage migration inhibitory factor is regulated by HIF-1α and cAMP and promotes renal cyst cell proliferation in a macrophage-independent manner - Safi, Wajima; Kraus, Andre; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (Journal of Molecular Medicine, 2020)
Abstract: Progressive cyst growth leads to decline of renal function in polycystic kidney disease. Macrophage migration inhibitory factor (MIF) was found to be upregulated in cyst-lining cells in a mouse model of polycystic kidney disease and to promote cyst growth. In addition, MIF can be secreted by tubular cells and may contribute to cyst growth in an autocrine manner. However, the underlying mechanisms leading to induction of MIF in cyst-lining cells remained elusive. Here, we demonstrate that hypoxia-inducible transcription factor (HIF) 1α upregulates MIF in cyst-lining cells in a tubule-specific PKD1 knockout mouse. Pharmacological stabilization of HIF-1α resulted in significant increase of MIF in cyst epithelial cells whereas tubule-specific knockout of HIF-1α prevented MIF upregulation. Identical regulation could be found for ABCA1, which has been shown to act as a transport protein for MIF. Furthermore, we show that MIF and ABCA1 are direct target genes of HIF-1α in human primary tubular cells. Next to HIF-1α and hypoxia, we found MIF being additionally regulated by cAMP which is a strong promotor of cyst growth. In line with these findings, HIF-1α- and cAMP-dependent in vitro cyst growth could be decreased by the MIF-inhibitor ISO-1 which resulted in reduced cyst cell proliferation. In conclusion, HIF-1α and cAMP regulate MIF in primary tubular cells and cyst-lining epithelial cells, and MIF promotes cyst growth in the absence of macrophages. In line with these findings, the MIF inhibitor ISO-1 attenuates HIF-1α- and cAMP-dependent in vitro cyst enlargement. Key messages: • MIF is upregulated in cyst-lining cells in a polycystic kidney disease mouse model. • MIF upregulation is mediated by hypoxia-inducible transcription factor (HIF) 1α. • ABCA1, transport protein for MIF, is also regulated by HIF-1α in vitro and in vivo. • MIF is additionally regulated by cAMP, a strong promotor of cyst growth. • MIF-inhibitor ISO-1 reduces HIF-1α- and cAMP-dependent cyst growth.
CRIS-Team Scopus Importer:2020-09-11
Keywords: cAMP; Hypoxia-inducible factor 1α; Macrophage migration inhibitory factor; Polycystic kidney disease

Nephron-specific knockout of TMEM16A leads to reduced number of glomeruli and albuminuria - Schenk, Laura K.; Buchholz, Björn; Henke, Sebastian F.; Michgehl, Ulf; Daniel, Christoph; Amann, Kerstin Ute; Kunzelmann, Karl; Pavenstaedt, Hermann (American Journal of Physiology-Renal Physiology, 2018)
TMEM16A is a transmembrane protein from a conserved family of calcium activated proteins, which is highly expressed in the kidney. TMEM16A confers calcium-activated chloride channel activity which is of importance for various cellular functions in secretory epithelia and involved in secretion-dependent renal cyst growth. However, its specific function in renal physiology has remained elusive so far. Therefore we generated conditional nephron specific TMEM16A knockout mice and found that these animals suffered from albuminuria. Kidney histology demonstrated an intact corticomedullary differentiation and absence of cysts. Electron microscopy showed a normal slit diaphragm. However, the total number of glomeruli and total nephron count was decreased in TMEM16A knockout animals. At the same time, glomerular diameter was increased, presumably as a result of the hyperfiltration in the remaining glomeruli. TUNEL and PCNA stainings showed increased cell death and increased proliferation. Proximal tubular cilia were intact in young animals but the number of properly ciliated cells was decreased in older, albuminuric animals. Taken together, our data suggests that TMEM16A may be involved in ureteric bud branching and proper nephron endowment. Loss of TMEM16A resulted in reduced nephron number and, subsequently, albuminuria and tubular damage.
EVALuna2:35395
Keywords: albuminuria; Ano1; kidney; nephron number; TMEM16A

P2Y2R and Cyst Growth in Polycystic Kidney Disease. - Kraus, Andre; Skoczynski, Kathrin; Brötsch, Martin; Burzlaff, Nicolai; Leipziger, Jens; Schiffer, Mario; Büttner-Herold, Maike; Buchholz, Björn (Journal of the American Society of Nephrology, 2024)
EVALuna2:569374

P2Y2R is a direct target of HIF-1α and mediates secretion-dependent cyst growth of renal cyst-forming epithelial cells - Kraus, Andre; Grampp, Steffen; Goppelt-Strübe, Margarete; Schreiber, Rainer; Kunzelmann, Karl; Peters, Dorien J. M.; Leipziger, Jens; Schley, Gunnar; Schödel, Johannes; Eckardt, Kai-Uwe; Buchholz, Björn (Purinergic Signalling, 2016)
Polycystic kidney diseases are characterized by numerous renal cysts that continuously enlarge resulting in compression of intact nephrons and tissue hypoxia. Recently, we have shown that hypoxia-inducible factor (HIF)-1 alpha promotes secretion-dependent cyst expansion, presumably by transcriptional regulation of proteins that are involved in calcium-activated chloride secretion. Here, we report that HIF-1 alpha directly activates expression of the purinergic receptor P2Y2R in human primary renal tubular cells. In addition, we found that P2Y2R is highly expressed in cyst-lining cells of human ADPKD kidneys as well as PKD1 orthologous mouse kidneys. Knockdown of P2Y2R in renal collecting duct cells inhibited calcium-dependent chloride secretion in Ussing chamber analyses. In line with these findings, knockdown of P2Y2R retarded cyst expansion in vitro and prevented ATP- and HIF-1 alpha-dependent cyst growth. In conclusion, P2Y2R mediates ATP-dependent cyst growth and is transcriptionally regulated by HIF-1 alpha. These findings provide further mechanistic evidence on how hypoxia promotes cyst growth.
EVALuna2:3913
Keywords: Polycystic kidney disease; Cyst growth; Chloride secretion; ATP; P2Y2R; Hypoxia; HIF-1 alpha

Pathogenic Relationships in Cystic Fibrosis and Renal Diseases: CFTR, SLC26A9 and Anoctamins - Kunzelmann, Karl; Ousingsawat, Jiraporn; Kraus, Andre; Park, Julien H.; Marquardt, Thorsten; Schreiber, Rainer; Buchholz, Björn (International Journal of Molecular Sciences, 2023)
The Cl−-transporting proteins CFTR, SLC26A9, and anoctamin (ANO1; ANO6) appear to have more in common than initially suspected, as they all participate in the pathogenic process and clinical outcomes of airway and renal diseases. In the present review, we will therefore concentrate on recent findings concerning electrolyte transport in the airways and kidneys, and the role of CFTR, SLC26A9, and the anoctamins ANO1 and ANO6. Special emphasis will be placed on cystic fibrosis and asthma, as well as renal alkalosis and polycystic kidney disease. In essence, we will summarize recent evidence indicating that CFTR is the only relevant secretory Cl− channel in airways under basal (nonstimulated) conditions and after stimulation by secretagogues. Information is provided on the expressions of ANO1 and ANO6, which are important for the correct expression and function of CFTR. In addition, there is evidence that the Cl− transporter SLC26A9 expressed in the airways may have a reabsorptive rather than a Cl−-secretory function. In the renal collecting ducts, bicarbonate secretion occurs through a synergistic action of CFTR and the Cl−/HCO3− transporter SLC26A4 (pendrin), which is probably supported by ANO1. Finally, in autosomal dominant polycystic kidney disease (ADPKD), the secretory function of CFTR in renal cyst formation may have been overestimated, whereas ANO1 and ANO6 have now been shown to be crucial in ADPKD and therefore represent new pharmacological targets for the treatment of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-09-15
Keywords: anoctamin; CFTR; pendrin; SLC26A9; TMEM16A; TMEM16F

PRECLINICAL EFFICACY OF DIRECT AMPK ACTIVATION WITH A NOVEL SMALL MOLECULE-PXL770-FOR THE TREATMENT OF AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE - Dagorn, Pascale Gluais; Buchholz, Björn; Bange, Hester; Blockken, Laura; Moller, David E.; Hallakou-Bozec, Sophie (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-07-22

Role of oxygen and the HIF-pathway in polycystic kidney disease - Buchholz, Björn; Eckardt, Kai-Uwe (Cellular Signalling, 2020)
Kidney cyst growth in ADPKD is associated with regional hypoxia, presumably due to a mismatch between enlarged cysts and the peritubular capillary blood supply and compression of peritubular capillaries in cyst walls. Regional hypoxia leads to activation of hypoxia-inducible transcription factors, with the two main HIF isoforms, HIF-1 and HIF-2 expressed in cyst epithelia and pericystic interstitial cells, respectively. While HIF-2 activation is linked to EPO production, mitigating the anemia that normally accompanies chronic kidney disease, HIF-1 promotes cyst growth. HIF-dependent cyst growth is primarily due to an increase in chloride-dependent fluid secretion into the cyst lumen. However, given the broad spectrum of HIF-target genes, additional HIF-mediated pathways may also contribute to cyst progression. Furthermore, hypoxia can influence cyst growth through the generation of reactive oxygen species. Since cyst expansion aggravates regional hypoxia, a feedforward loop is established that accelerates cyst expansion and disease progression. Inhibiting the HIF pathway and/or HIF target genes that are of particular relevance for HIF-dependent cyst fluid secretion may therefore represent novel therapeutic approaches to retard the progression of APDKD.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Autosomal dominant polycystic kidney disease; ADPKD; Hypoxia; Hypoxia-inducible factor; HIF; Polycystic kidney disease; PKD

Role of TMEM16 proteins in polycystic kidney disease - Cabrita, I.; Buchholz, Björn; Ousingsawat, J.; Kunzelmann, K.; Schreiber, R. (Acta Physiologica, 2019)

Severe neurological outcomes after very early bilateral nephrectomies in patients with autosomal recessive polycystic kidney disease (ARPKD) - Burgmaier, Kathrin; Ariceta, Gema; Bald, Martin; Buescher, Anja Katrin; Burgmaier, Mathias; Erger, Florian; Gessner, Michaela; Gokce, Ibrahim; König, Jens; Kowalewska, Claudia; Massella, Laura; Mastrangelo, Antonio; et al. (Scientific Reports, 2020)
To test the association between bilateral nephrectomies in patients with autosomal recessive polycystic kidney disease (ARPKD) and long-term clinical outcome and to identify risk factors for severe outcomes, a dataset comprising 504 patients from the international registry study ARegPKD was analyzed for characteristics and complications of patients with very early (≤ 3 months; VEBNE) and early (4–15 months; EBNE) bilateral nephrectomies. Patients with very early dialysis (VED, onset ≤ 3 months) without bilateral nephrectomies and patients with total kidney volumes (TKV) comparable to VEBNE infants served as additional control groups. We identified 19 children with VEBNE, 9 with EBNE, 12 with VED and 11 in the TKV control group. VEBNE patients suffered more frequently from severe neurological complications in comparison to all control patients. Very early bilateral nephrectomies and documentation of severe hypotensive episodes were independent risk factors for severe neurological complications. Bilateral nephrectomies within the first 3 months of life are associated with a risk of severe neurological complications later in life. Our data support a very cautious indication of very early bilateral nephrectomies in ARPKD, especially in patients with residual kidney function, and emphasize the importance of avoiding severe hypotensive episodes in this at-risk cohort.
CRIS-Team Scopus Importer:2020-10-16

Significance of Glomerular Immune Reactivity in Time Zero Biopsies for Allograft Survival Beyond IgA - Vonbrunn, Eva; Serikova, Sofya; Daniel, Christoph; Amann, Kerstin Ute; Schödel, Johannes; Buchholz, Björn; Ferrazzi, Fulvia; Heller, Katharina M.; Apel, Hendrik; Büttner-Herold, Maike (Frontiers in Medicine, 2021)
The quality of a renal transplant can influence the clinical course after transplantation. Glomerular immune reactivity in renal transplants has previously been described, focusing particularly on IgA, and has been shown to disappear in most cases without affecting the outcome. Here, we describe a cohort of time zero biopsies with regard to glomerular immune reactivity and implications for histomorphology and follow-up. 204 Time zero biopsies were analyzed by immunohistochemistry for glomerular immune reactivity. Time zero and 1-year biopsies were evaluated for histomorphological changes, which, together with clinical and follow-up data, were assessed for associations with glomerular immune profiles. Nearly half of the analyzed time zero biopsies showed glomerular immune reactivity with mesangial C3 being the most common (32.9%), followed by IgA (13.7%) and fullhouse patterns (6.9%). Strong C3 deposits (C3high) were only observed in deceased transplants. In the majority of cases immune reactivity was undetectable in follow-up biopsies and had no adverse effect on transplant function in follow-up of 5 years. In kidney pairs transplanted to different recipients a strong concordance of immune profiles in both kidneys was observed. Moreover, an association of male donor sex and deceased donor transplantation with the presence of immune reactivity was observed. In conclusion, glomerular immune reactivity is a very frequent finding in time zero biopsies, which seems to be determined by donor parameters including male sex and deceased donor transplants. It had no adverse impact on transplant function in 5-year follow-up. Glomerular immune reactivity in time zero biopsies, therefore, does not appear to indicate an inferior quality of the transplant.
CRIS-Team WoS Importer:2021-04-30
Keywords: complement; renal tranplantation; time zero biopsy; transplant quality; immune reactivity

The chloride channel CFTR is not required for cyst growth in an ADPKD mouse model - Talbi, Khaoula; Cabrita, Inês; Kraus, Andre; Hofmann, Sascha; Skoczynski, Kathrin; Kunzelmann, Karl; Buchholz, Björn; Schreiber, Rainer (The FASEB Journal, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by the development of bilateral renal cysts which enlarge continuously, leading to compression of adjacent intact nephrons. The growing cysts lead to a progressive decline in renal function. Cyst growth is driven by enhanced cell proliferation and chloride secretion into the cyst lumen. Chloride secretion is believed to occur mainly by the cAMP-activated cystic fibrosis transmembrane conductance regulator (CFTR), with some contribution by the calcium-activated chloride channel TMEM16A. However, our previous work suggested TMEM16A as a major factor for renal cyst formation. The contribution of CFTR to cyst formation has never been demonstrated in an adult ADPKD mouse model. We used mice with an inducible tubule-specific Pkd1 knockout, which consistently develop polycystic kidneys upon deletion of Pkd1. Cellular properties, ion currents, and cyst development in these mice were compared with that of mice carrying a co-deletion of Pkd1 and Cftr. Knockout of Cftr did not reveal any significant impact on cyst formation in the ADPKD mouse model. Furthermore, knockout of Cftr did not attenuate the largely augmented cell proliferation observed in Pkd1 knockout kidneys. Patch clamp analysis on primary renal epithelial cells lacking expression of Pkd1 indicated an only marginal contribution of CFTR to whole cell Cl− currents, which were clearly dominated by calcium-activated TMEM16A currents. In conclusion, CFTR does not essentially contribute to renal cyst formation in mice caused by deletion of Pkd1. Enhanced cell proliferation and chloride secretion is caused primarily by upregulation of the calcium-activated chloride channel TMEM16A.
CRIS-Team Scopus Importer:2021-10-08
Keywords: ADPKD; CFTR; cyst growth; proliferation; TMEM16A

The extracellular matrix protein fibronectin promotes metanephric kidney development - Skoczynski, Kathrin; Kraus, Andre; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute; Schiffer, Mario; Hermann, Kristina; Herrnberger-Eimer, Leonie; Tamm, Ernst R.; Buchholz, Björn (Pflügers Archiv: European Journal of Physiology, 2024)
Complex interactions of the branching ureteric bud (UB) and surrounding mesenchymal cells during metanephric kidney development determine the final number of nephrons. Impaired nephron endowment predisposes to arterial hypertension and chronic kidney disease. In the kidney, extracellular matrix (ECM) proteins are usually regarded as acellular scaffolds or as the common histological end-point of chronic kidney diseases. Since only little is known about their physiological role in kidney development, we aimed for analyzing the expression and role of fibronectin. In mouse, fibronectin was expressed during all stages of kidney development with significant changes over time. At embryonic day (E) 12.5 and E13.5, fibronectin lined the UB epithelium, which became less pronounced at E16.5 and then switched to a glomerular expression in the postnatal and adult kidneys. Similar results were obtained in human kidneys. Deletion of fibronectin at E13.5 in cultured metanephric mouse kidneys resulted in reduced kidney sizes and impaired glomerulogenesis following reduced cell proliferation and branching of the UB epithelium. Fibronectin colocalized with alpha 8 integrin and fibronectin loss caused a reduction in alpha 8 integrin expression, release of glial-derived neurotrophic factor and expression of Wnt11, both of which are promoters of UB branching. In conclusion, the ECM protein fibronectin acts as a regulator of kidney development and is a determinant of the final nephron number.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Alpha 8 integrin; Branching; Fibronectin; Kidney development; Nephron number

The impact of chloride secretion on the progression of polycystic kidney disease - Kraus, Andre; Faria, D.; Schley, Gunnar; Schödel, Johannes; Grampp, S.; Peters, D. J.; Schreiber, R.; Kunzelmann, K.; Eckardt, Kai-Uwe; Buchholz, Björn (Acta Physiologica, 2019)

The impact of hypoxia on nephrogenesis - Buchholz, Björn; Schley, Gunnar; Eckardt, Kai-Uwe (Current Opinion in Nephrology and Hypertension, 2016)
Purpose of reviewKidney development depends on outgrowth of the ureteric bud into the metanephric mesenchyme. The number of ureteric bud branching events determines the final number of nephrons, which correlates inversely with the risk for development of chronic kidney disease and arterial hypertension during lifetime. The purpose of this review is to highlight the influence of oxygen on nephrogenesis and to describe cellular mechanisms by which hypoxia can impair nephron formation.Recent findingsAlthough kidney development normally takes place under hypoxic conditions, nephrogenesis is impaired when oxygen availability falls below the usual range. Hypoxia-inducible factors (HIF) play an important role in linking low oxygen concentrations to the biology of nephron formation, but their effect appears to be cell type dependent. In ureteric bud cells, HIF stimulates tubulogenesis, whereas HIF stabilization in cells of the metanephric mesenchyme results in secretion of growth factors, including vascular endothelial growth factor A, which in aggregate inhibit ureteric bud branching. The balance between pro and antibranching effects may be altered in various ways, but the inhibitory effect usually seems to predominate under reduced oxygen concentrations, explaining how intrauterine hypoxia can lead to low nephron numbers.SummaryOxygen availability has a complex influence on nephrogenesis. Oxygen concentrations outside an optimal low range may affect nephron endowment. Associations between placental insufficiency and increased risk for chronic kidney disease and arterial hypertension during later life may to a large extent be due to direct effects of reduced oxygen supply to the metanephric mesenchyme and mediated through the HIF pathway.
Keywords: chronic kidney disease; hypoxia; hypoxia-inducible factor-1 alpha; kidney development; nephron number

The impact of hypoxia on nephrogenesis - Buchholz, Björn; Schley, Gunnar; Eckardt, Kai-Uwe (Current Opinion in Nephrology and Hypertension, 2016)
Kidney development depends on outgrowth of the ureteric bud into the metanephric mesenchyme. The number of ureteric bud branching events determines the final number of nephrons, which correlates inversely with the risk for development of chronic kidney disease and arterial hypertension during lifetime. The purpose of this review is to highlight the influence of oxygen on nephrogenesis and to describe cellular mechanisms by which hypoxia can impair nephron formation.Although kidney development normally takes place under hypoxic conditions, nephrogenesis is impaired when oxygen availability falls below the usual range. Hypoxia-inducible factors (HIF) play an important role in linking low oxygen concentrations to the biology of nephron formation, but their effect appears to be cell type dependent. In ureteric bud cells, HIF stimulates tubulogenesis, whereas HIF stabilization in cells of the metanephric mesenchyme results in secretion of growth factors, including vascular endothelial growth factor A, which in aggregate inhibit ureteric bud branching. The balance between pro and antibranching effects may be altered in various ways, but the inhibitory effect usually seems to predominate under reduced oxygen concentrations, explaining how intrauterine hypoxia can lead to low nephron numbers.Oxygen availability has a complex influence on nephrogenesis. Oxygen concentrations outside an optimal low range may affect nephron endowment. Associations between placental insufficiency and increased risk for chronic kidney disease and arterial hypertension during later life may to a large extent be due to direct effects of reduced oxygen supply to the metanephric mesenchyme and mediated through the HIF pathway.
EVALuna2:3856

The Raf kinase inhibitor PLX5568 slows cyst proliferation in rat polycystic kidney disease but promotes renal and hepatic fibrosis - Buchholz, Björn; Klanke, Bernd; Schley, Gunnar; Bollag, Gideon; Tsai, James; Kroening, Sven; Yoshihara, Daisuke; Wallace, Darren P.; Kraenzlin, Bettina; Gretz, Norbert; Hirth, Peter; Eckardt, Kai-Uwe; et al. (Nephrology Dialysis Transplantation, 2011)
Background. Autosomal dominant polycystic kidney disease (ADPKD) is a common cause of renal failure. Aberrant epithelial cell proliferation is a major cause of progressive cyst enlargement in ADPKD. Since activation of the Ras/Raf signaling system has been detected in cyst-lining epithelia, inhibition of Raf kinase has been proposed as an approach to retard the progression of ADPKD.Methods and results. PLX5568, a novel selective small molecule inhibitor of Raf kinases, attenuated proliferation of human ADPKD cyst epithelial cells. It reduced in vitro cyst growth of Madin-Darby Canine Kidney cells and of human ADPKD cells within a collagen gel. In male cy/1 rats with polycystic kidneys, PLX5568 inhibited renal cyst growth along with a significant reduction in the number of proliferating cell nuclear antigen-and phosphorylated extracellular signal-regulated kinase-positive cyst-lining epithelial cells. Furthermore, treated animals showed increased capacity to concentrate urine. However, PLX5568 did not lead to a consistent improvement of renal function. Moreover, although relative cyst volume was decreased, total kidney-to-body weight ratio was not significantly reduced by PLX5568. Further analyses revealed a 2-fold increase of renal and hepatic fibrosis in animals treated with PLX5568.Conclusions. PLX5568 attenuated cyst enlargement in vitro and in a rat model of ADPKD without improving kidney function, presumably due to increased renal fibrosis. These data suggest that effective therapies for the treatment of ADPKD will need to target fibrosis as well as the growth of cysts.
Keywords: ERK; polycystic kidney disease; proliferation; Raf

The role of HIF-1 alpha in the pathogenesis of psoriasis - Das Mahapatra, K.; Jargosch, M.; Hillig, C.; Buchholz, Björn; Thomas, J.; Eyerich, S.; Eyerich, K.; Garzorz-Stark, N. (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-03-10

TMEM16A drives renal cyst growth by augmenting Ca2+ signaling in M1 cells - Cabrita, Ines; Buchholz, Björn; Schreiber, Rainer; Kunzelmann, Karl (Journal of Molecular Medicine, 2020)
Abstract: Polycystic kidney disease (PKD) leads to continuous decline of renal function by growth of renal cysts. Enhanced proliferation and transepithelial chloride secretion through cystic fibrosis transmembrane conductance regulator (CFTR) and Ca2+-activated TMEM16A Cl− channels is thought to cause an increase in cyst volume. Recent work shows the pro-proliferative role of the Ca2+ activated Cl− channel TMEM16A (anoctamin 1), and demonstrates the essential contribution of TMEM16A to CFTR-dependent Cl− secretion. The present data demonstrate an increase in intracellular Ca2+ ([Ca2+]i) signals and Cl− secretion by TMEM16A, in renal collecting duct principle cells from dog (MDCK) and mouse (M1) as well as primary tubular epithelial cells from PKD1−/− knockout mice. M1 organoids proliferated, increased expression of TMEM16A, and secreted Cl− upon knockdown of endogenous polycystin 1 or 2 (PKD1,2), by retroviral transfection with shPKD1 and shPKD2, respectively. Knockdown of PKD1 or PKD2 increased basal intracellular Ca2+ levels and enhanced purinergic Ca2+ release from endoplasmic reticulum. In contrast, ryanodine receptors were found not to be expressed in mouse renal epithelial cells and caffeine had no effects on [Ca2+]i. Ca2+ signals, proliferation, and Cl− secretion were largely reduced by knockdown or blockade of TMEM16A. TMEM16A may be therefore important for enhanced Ca2+ release from IP3-sensitive Ca2+ stores in polycystic kidney disease. Key messages: • ADPKD leads to continuous decline of renal function by growth of renal cysts. • Knockdown of PKD1 or PKD2 increases TMEM16A expression. • TMEM16A enhanced intracellular Ca2+ signals, Cl− secretion, and proliferation. • TMEM16A contributes to cyst growth in ADPKD.
CRIS-Team Scopus Importer:2020-03-27
Keywords: ADPKD; Anoctamin 1; Ca; Renal cysts; TMEM16A

Trafficking of TRPP2 by PACS proteins represents a novel mechanism of ion channel regulation - Koettgen, Michael; Benzing, Thomas; Simmen, Thomas; Tauber, Robert; Buchholz, Björn; Feliciangeli, Sylvain; Huber, Tobias B.; Schermer, Bernhard; Kramer-Zucker, Albrecht; Höpker, Katja; Simmen, Katia Carmine; Tschucke, Christoph Carl; et al. (EMBO Journal, 2005)
The trafficking of ion channels to the plasma membrane is tightly controlled to ensure the proper regulation of intracellular ion homeostasis and signal transduction. Mutations of polycystin- 2, a member of the TRP family of cation channels, cause autosomal dominant polycystic kidney disease, a disorder characterized by renal cysts and progressive renal failure. Polycystin- 2 functions as a calcium- permeable nonselective cation channel; however, it is disputed whether polycystin- 2 resides and acts at the plasma membrane or endoplasmic reticulum ( ER). We show that the subcellular localization and function of polycystin- 2 are directed by phosphofurin acidic cluster sorting protein ( PACS)- 1 and PACS- 2, two adaptor proteins that recognize an acidic cluster in the carboxy- terminal domain of polycystin- 2. Binding to these adaptor proteins is regulated by the phosphorylation of polycystin- 2 by the protein kinase casein kinase 2, required for the routing of polycystin- 2 between ER, Golgi and plasma membrane compartments. Our paradigm that polycystin- 2 is sorted to and active at both ER and plasma membrane reconciles the previously incongruent views of its localization and function. Furthermore, PACS proteins may represent a novel molecular mechanism for ion channel trafficking, directing acidic cluster- containing ion channels to distinct subcellular compartments.
Keywords: PACS; polycystin-2; TRPP2

TRPP2 and TRPV4 form a polymodal sensory channel complex - Koettgen, Michael; Buchholz, Björn; Buchholz, Bjoern; Garcia-Gonzalez, Miguel A.; Kotsis, Fruzsina; Fu, Xiao; Doerken, Mara; Boehlke, Christopher; Steffl, Daniel; Tauber, Robert; Wegierski, Tomasz; Nitschke, Roland; et al. (The Journal of Cell Biology, 2008)
The primary cilium has evolved as a multifunctional cellular compartment that decorates most vertebrate cells. Cilia sense mechanical stimuli in various organs, but the molecular mechanisms that convert the deflection of cilia into intracellular calcium transients have remained elusive. Polycystin-2 (TRPP2), an ion channel mutated in polycystic kidney disease, is required for ciliamediated calcium transients but lacks mechanosensitive properties. We find here that TRPP2 utilizes TRPV4 to form a mechano- and thermosensitive molecular sensor in the cilium. Depletion of TRPV4 in renal epithelial cells abolishes flow-induced calcium transients, demonstrating that TRPV4, like TRPP2, is an essential component of the ciliary mechanosensor. Because TRPV4-deficient zebrafish and mice lack renal cysts, our findings challenge the concept that defective ciliary flow sensing constitutes the fundamental mechanism of cystogenesis.

TRPP2 CHANNELS AND POLYCYSTIC KIDNEY DISEASE: CALCIUM SIGNALING AND CELL DEATH - Kottgen, Michael; Wegierski, Tomasz; Steffl, Daniel; Kopp, Christoph; Buchholz, Björn; Tauber, Robert; Walz, Gerd; Watnick, Terry; Montell, Craig (Journal of Physiological Sciences, 2009)

TRPP2 channels regulate apoptosis through the Ca2+ concentration in the endoplasmic reticulum - Wegierski, Tomasz; Steffl, Daniel; Kopp, Christoph; Tauber, Robert; Buchholz, Björn; Nitschke, Roland; Kuehn, E. Wolfgang; Walz, Gerd; Koettgen, Michael (EMBO Journal, 2009)
Ca2+ is an important signalling molecule that regulates multiple cellular processes, including apoptosis. Although Ca2+ influx through transient receptor potential (TRP) channels in the plasma membrane is known to trigger cell death, the function of intracellular TRP proteins in the regulation of Ca2+-dependent signalling pathways and apoptosis has remained elusive. Here, we show that TRPP2, the ion channel mutated in autosomal dominant polycystic kidney disease (ADPKD), protects cells from apoptosis by lowering the Ca2+ concentration in the endoplasmic reticulum (ER). ER-resident TRPP2 counteracts the activity of the sarcoendoplasmic Ca2+ ATPase by increasing the ER Ca2+ permeability. This results in diminished cytosolic and mitochondrial Ca2+ signals upon stimulation of inositol 1,4,5-trisphosphate receptors and reduces Ca2+ release from the ER in response to apoptotic stimuli. Conversely, knockdown of TRPP2 in renal epithelial cells increases ER Ca2+ release and augments sensitivity to apoptosis. Our findings indicate an important function of ER-resident TRPP2 in the modulation of intracellular Ca2+ signalling, and provide a molecular mechanism for the increased apoptosis rates in ADPKD upon loss of TRPP2 channel function.
Keywords: calcium; ER; gateway; mitochondria; polycystin-2

Ultra high frequency ultrasound enables real-time visualization of blood supply from chorioallantoic membrane to human autosomal dominant polycystic kidney tissue - Schueler, Jan; Kuenzel, Jonas; Thuesing, Anna; Pion, Eric; Behncke, Rose Yinghan; Haegerling, Rene; Fuchs, Dieter; Kraus, Andre; Buchholz, Björn; Huang, Boqiang; Merhof, Dorit; Werner, Jens M.; et al. (Scientific Reports, 2024)
Ultra high frequency (UHF) ultrasound enables the visualization of very small structures that cannot be detected by conventional ultrasound. The utilization of UHF imaging as a new imaging technique for the 3D-in-vivo chorioallantoic membrane (CAM) model can facilitate new insights into tissue perfusion and survival. Therefore, human renal cystic tissue was grafted onto the CAM and examined using UHF ultrasound imaging. Due to the unprecedented resolution of UHF ultrasound, it was possible to visualize microvessels, their development, and the formation of anastomoses. This enabled the observation of anastomoses between human and chicken vessels only 12 h after transplantation. These observations were validated by 3D reconstructions from a light sheet microscopy image stack, indocyanine green angiography, and histological analysis. Contrary to the assumption that the nutrient supply of the human cystic tissue and the gas exchange happens through diffusion from CAM vessels, this study shows that the vasculature of the human cystic tissue is directly connected to the blood vessels of the CAM and perfusion is established within a short period. Therefore, this in-vivo model combined with UHF imaging appears to be the ideal platform for studying the effects of intravenously applied therapeutics to inhibit renal cyst growth.
CRIS-Team Scopus Importer:2024-05-10